Selected Lectures of the 2nd Course of Perinatal and Pediatric Cardiology; Cagliari (Italy); October 19, 2022 - - (Hygeia Press di Corridori Marinella, 2022)
Selected Lectures of the 2nd Course of Perinatal and Pediatric Cardiology; Cagliari (Italy);  October 19th, 2022   The 2nd Course of Perinatal and Pediatric Cardiology is a Satellite Meeting of the 18th International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 19th-22nd, 2022.   LECT 1. CONGENITAL HEART MALFORMATIONS AND EXTRACARDIAC ABNOMALITIES • A. Atzei, P. Neroni, M.I. Joswig, V. Fanos (Cagliari, Italy) LECT 2. WHEN TO SUSPECT A CONGENITAL HEART DISEASE IN UTERO • S. Sanna, M.L. Fais, A. Melis, S. Angioni (Cagliari, Italy) LECT 3. DIAGNOSIS AND MANAGEMENT OF FETAL AND NEONATAL CARDIAC ARRHYTHMIAS • E. Rosati (Tricase [BA], Italy) LECT 4. WHEN THE DUCTUS OF BOTALLO REVEALS ITSELF TO BE A FRIEND: HOW TO GUARANTEE ITS PATENCY • M. Chessa (Milan, Italy) LECT 5. PATENT DUCTUS ARTERIOSUS: THE HIDDEN ENEMY. HOW CAN WE TREAT IT? • C. Spiga, R. Mazzitti, M. Melis, E. Curridori, D. Manus, R. Pintus, P. Neroni, V. Fanos (Cagliari, Italy) LECT 6. TRANSCATHETER CLOSURE OF PATENT DUCTUS ARTERIOSUS IN PREMATURE BABIES • G. Butera (Rome, Italy) LECT 7. BRONCHODYSPLASIA AND PULMONARY HYPERTENSION • F. Mecarini, P. Neroni, A. Atzei, C. Pintus, V. Masile, V. Fanos (Cagliari, Italy) LECT 8. COUNSELLING OF CONGENITAL HEART DISEASE • P. Neroni, A. Atzei, R. Pintus, V. Masile, V. Fanos (Cagliari, Italy) LECT 9. THE CARE OF THE RELATIONSHIPS BETWEEN SOCIAL-HEALTH WORKERS AND PARENTS FOLLOWING THE COMMUNICATION OF A PERINATAL DIAGNOSIS OF CONGENITAL MALFORMATION • M. Mastinu (Cagliari, Italy) LECT 10. OBSTETRICAL MANAGEMENT OF FETUS WITH HEART DEFECTS • S. Ajossa, M.L. Robuschi, V. Taccori, L. Suzzi, S. Guerriero (Cagliari, Italy) LECT 11. GENETICS OF CONGENITAL HEART DISEASE • G. Beffagna, D. Colavito, A. Leon (Padua, Italy)